The Empty Tomb and the Resurrection Debate: Can a Starting Point be Established for Studying the Easter Events? - Beresh, Nathan (My University, 2018)
Scholars Gary Habermas and Michael Licona have created a research approach to study the historicity of Jesus’s resurrection called “historical bedrock.” This approach seeks to gather highly attested information about the Easter events that are agreed upon by the majority of scholars and then use this information as a starting point in studying the resurrection. A piece of information noticeably missing from the historical bedrock list is the empty tomb. By using the empty tomb as a case study, this thesis is a critical analysis of Habermas and Licona’s historical bedrock approach. In it, I propose that historical bedrock be amended to what I call “baseline information.” Baseline information differs from Habermas and Licona’s approach in that less emphasis is placed on the role of scholarly consensus and the title does not convey the notion that the data within it is unquestionably historical.
Keywords: Historical Bedrock; Empty Tomb; Resurrection; Baseline Information